2009
DOI: 10.1175/2008jcli2488.1
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between Sea Surface Temperature and Low-Level Winds in Mesoscale Numerical Models

Abstract: This study evaluates the impacts of sea surface temperature (SST) specification and grid resolution on numerical simulations of air-sea coupling near oceanic fronts through analyses of surface winds from the European Centre for Medium-Range Weather Forecasts (ECMWF) model. The 9 May 2001 change of the boundary condition from the Reynolds SST analyses to the NOAA Real-Time Global (RTG) SST in the ECMWF model resulted in an abrupt increase in mesoscale variance of the model surface winds over the ocean. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 39 publications
10
104
0
Order By: Relevance
“…In addition, Chelton et al (2006) found that fine-scale wind structure in the atmospheric boundary layer is underestimated even in high resolution models driven by high resolution SSTs, and Song et al (2009) have shown that this arises due to an underestimate of vertical diffusion in the boundary layer. Although these studies used different models to that used here, it is possible that limitations in the boundary layer scheme could also be leading to an underestimate of the sensitivity of the storm track to SST resolution in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Chelton et al (2006) found that fine-scale wind structure in the atmospheric boundary layer is underestimated even in high resolution models driven by high resolution SSTs, and Song et al (2009) have shown that this arises due to an underestimate of vertical diffusion in the boundary layer. Although these studies used different models to that used here, it is possible that limitations in the boundary layer scheme could also be leading to an underestimate of the sensitivity of the storm track to SST resolution in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The intense heat flux over the K-KE is adequately represented in JRA-25 regarding its distribution and amplitude. While we will not pursue the exact cause of JRA-25 differences from ICOADS, we found, by analyzing other reanalysis datasets, that this problem is general, indicating problems of current assimilating AGCMs in representation of physics, especially those for MABL (Song et al 2009). …”
Section: Jra-25mentioning
confidence: 93%
“…More recently, Minobe et al (2008Minobe et al ( , 2010 suggest that the hydrostatic adjustment along the Gulf Stream leads to convective cloud formation and enhanced precipitation. Song et al(2006) show that, based on the RAM experiments, pressure gradient across the Gulf Stream front is main force modifying the surface winds. Xu et al (2010) also detected a hydrostatic effect over the cool water pool formed between the Pacific coast of Japan and the large meander of the Kuroshio.…”
Section: Introductionmentioning
confidence: 91%
“…This ocean-atmosphere interaction is clearly evident in the surface winds in operational weather forecast models [73], but is underestimated by about a factor of two because of deficiencies in the parameterization of atmospheric vertical mixing [102]. Observations [68] and mesoscale models with sufficient sensitivity of vertical mixing to stability reveal that the SST influence extends throughout the troposphere in all of the dynamic fields, e.g., the vertical velocity (Fig.…”
Section: Response To Sstsmentioning
confidence: 97%